Measuring cognitive change in subjects with prodromal Alzheimer's disease. Issue 4 (9th July 2013) - Mura, T; Proust-Lima, C; Jacqmin-Gadda, H; Akbaraly, T N; Touchon, J; Dubois, B; Berr, C
Abstract : Objective: To investigate the sensitivity of a large set of neuropsychological tests to detect cognitive changes due to prodromal Alzheimer's disease(AD); to compare their metrological properties in order to select a restricted number of these tests for the longitudinal follow-up of subjects with prodromal AD. Participants: 212 patients with mild cognitive impairment were tested at baseline by a standardised neuropsychological battery, which included: the Free and Cued Selective Reminding test (FCSRT), the Benton Visual Retention test, the Deno100, verbal fluency, a serial digit learning test, the double task of Baddeley, the Wechsler Adult Intelligence Scale (WAIS) similarities, the Trail-Making Test and the WAIS digit symbol test. Patients were monitored every 6 months for up to 3 years in order to identify those who converted to AD (retrospectively classified as prodromal AD). Statistical analyses were performed using a nonlinear multivariate mixed model involving a latent process. This model assumes that the psychometric tests are nonlinear transformations of a common latent cognitive process, and it captures the metrological properties of tests. Results: 57 patients converted to AD. The most sensitive tests in the detection of cognitive changes due to prodromal AD were the FCSRT, the semantic verbal fluency and the Deno100. Some tests exhibited a higher sensitivity to cognitive changes for subjects with high levels of cognition, such as the free recall, delayed free recall scores of the FCSRT and the semantic verbal fluency, whereas others showed a higher sensitivity at low levels of cognition, such as the total recall score of the FCSRT. Conclusions: Tests used for the follow-up of prodromal AD subjects should be chosen among those that actually decline in this stage of the disease and should be selected according to the subject's initial scores.